NEW RECORD OF HOST PLANTS AND MITE PARASITE OF AGRAPHOPUS SP. (COREOIDEA : RHOPALIDAE). - DHIMAN, S. C.; SINGH, R. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Two new host plants, viz. Cynodon dactylon and Cyprus rotundus, of Agraphopus sp are recorde ed. Also, an Acarine ectoparasite, Leptus sp. of this bug has been reported. The extent of parasitization is found 45 to 90 per cent and load of Leptus sp. larvae per bug is seen 1 as minimum and 6 as maximum.